Decomposition Factors Household Energy Subsidy Consumption in Indonesia: Kaya Identity and Logarithmic Mean Divisia Index Approach - Sudarmaji, Eka; Achsani, Noer Azam; Arkeman, Yandra; Fahmi, Idqan (International Journal of Energy Economics and Policy, 2022)
For decades, the subsidy had prompted excessive and wasteful while offering little motivation to boost energy efficiency or reduce domestic greenhouse gas emissions. This paper aimed to measure household subsidy energy by examining the relationship between the other ten variables. The Logarithmic Mean Divisia Index (LMDI) and decomposition index were deployed to recognize the determinant effects that drive household’s subsidy energy consumption. This study also presented an ARDL model applied. The robustness of the Granger Causality, Long-run, and Short-run causality during 1990-2017 was assessed. Based on LMDI, we found out that Population, Income Per Capita, Ratio National Renewal Energy over Fuel Fossil, Gross Capital Stock, Urban Household Consumption, and Ratio Household Subsidy were the positive factors that aggravate the change in household energy subsidy. The negative sign of Ratio National Energy Intensity effect, Ratio Fossil Renewal Energy effect, Ratio Capital Labour substitution, and Ratio Household over Labour Force signified the decreasing significance of less household energy subsidy. On the ECM, we identified a negative sign speed-of-adjustment and significant at 1%. It implied that all the ten variable effects were converging in the long run after an experience shocks. The equation parameters were considered stable since the CUSUM gets inside the two critical lines. Additional RESET test of the stability to ascertain whether the estimated model was linear or correctly specified has been performed.